IMPLEMENTASI PENDEKATAN SUPERVISI PENDIDIKAN DALAM PERBAIKAN PEMBELAJARAN DI SMP ISLAM TERPADU AN-NUR - Oktavia, Amalia; Zubaidah, ST; Metroyadi; Sakka, Ambo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Educational supervision aims to improve teacher professionalism, but its implementation is often suboptimal due to its administrative nature. Time constraints and minimal follow-up result in teachers' lack of reflection on learning. As a result, learning tends to be monotonous and less innovative. This study aims to analyze the implementation of the educational supervision approach in efforts to improve learning at An-Nur Integrated Islamic Junior High School. This study used a qualitative method with a descriptive approach. Data were obtained through interviews, observation, and documentation techniques involving the principal and teachers as research informants. The data obtained were then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results show that the implementation of the educational supervision approach at An-Nur Integrated Islamic Junior High School is carried out through supervision planning activities, conducting learning observations, and providing feedback to teachers. The implementation of this supervision has a positive impact on improving the quality of learning, particularly in lesson planning, the use of more varied methods, and improving teachers' professional competence. Therefore, supervision needs to be implemented continuously with clear follow-up to optimize its impact. In addition, a more collaborative approach is needed so that teachers can be more active in developing learning innovations.